A comparison of the substantive aspects of impermissible tax arrangements under South Africa's General Anti-Avoidance Rule and the Principal Purpose Test with specific reference to the examples found within the 2017 OECD Model Tax Convention - Zebert, Bradley Arthur (Department of Commercial Law, 2022)
The Organisation for Economic Cooperation and Development released the 2017 Model Tax Convention on Income and on Capital (hereafter "Convention") which contains a Principal Purpose Test under article 29(9). The practical application of this test is explained with the use of various examples within the accompanying commentary to the Convention. However, various ambiguities both in the Convention and the accompanying commentary exist. The author raises these ambiguities and contrasts them with the general anti-avoidance rule (hereafter "GAAR") found within S80A of the Income Tax Act 8 of 1962. In doing so, the author asked which areas of the Principal Purpose Test are vague and can be interpreted in light of the South African GAAR to assist with attributing a meaning to it. The key findings from this paper identified various areas of the Principal Purpose Test where the GAAR could be used to assist in the interpretation and application of the Principal Purpose Test being the phrases "the principal purpose", "benefit" and "arrangement". Other areas of ambiguity which were also interpreted with the assistance of the GAAR related to whether the Principal Purpose Test contained a business reality test as well as the further aspects of the test relating to its interpretative aspect, subjective enquiry and burden of proof. It was argued that these areas may indicate how the South African courts may apply the Principal Purpose Test in the South African context.